A meta-analysis of efficacy on dexamethasone and clomiphene in the treatment of polycystic ovary syndrome patients - Ying Sha; Jianfen Zhu; Fangrong Shen (BMC, 2024)
Abstract Objective Polycystic ovary syndrome (PCOS) is an endocrine gynecological disease affecting many women of reproductive age. Clomiphene is the first-line treatment for PCOS patients, but most individuals may be resistant to it. This study aims to assess the efficacy of dexamethasone and clomiphene in the treatment of PCOS patients, and to provide a theoretical basis for clinicians to study and treat PCOS. Methods Chinese and English databases including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), WanFang Medical Network, and VIP Information Chinese Journal Service Platform (VIP) were searched from the inception to January 2023. Review Manager and Stata software were used for meta- analysis. The risk of bias of eligible studies were assessed using Cochrane's risk of bias tool. Publication bias was assessed by funnel plots, Begg's and Egger's tests. Results A total of 12 literatures were finally included, with a total of 1270 PCOS patients. Compared with the control group, dexamethasone combined with clomiphene could significantly improve pregnancy (RR = 1.71, P < 0.00001), ovulation (RR = 1.30, P < 0.00001), luteinizing hormone level (SMD = -0.94, P < 0.00001), estradiol level (SMD = 0.99, P = 0.05), progesterone level (SMD = 5.08, P = 0.002) and testosterone level (SMD = -1.59, P < 0.00001). However, there were no significant effects on ovulation-stimulating hormone level (SMD = 0.15, P = 0.37), adverse reactions (RR = 1.30, P = 0.30), dizziness (RR = 1.50, P = 0.45), and vomiting (RR = 1.67, P = 0.48). Conclusion The treatment of dexamethasone combined with clomiphene is helpful to improve the ovulation and pregnancy rate in patients with PCOS, and improve the hormone levels of patients.